(untitled) (Globalization and Business, 2023)
The coronavirus pandemic almost immediately led to a global narrowing of the global economy, a sharp reduction in aggregate supply and demand. The decline in production was especially felt in the second quarter of 2020, when the recession in most countries of the world had a double-digit value. According to IMF forecasts, in general, the economy in developed countries, even in 2021, will not reach the level of 2019. The global economic downturn is accompanied by a massive reduction in jobs, rising unemployment, especially in industries that are focused on foreign markets and serving foreign consumers (export production, reception and service of foreign tourists, international transportation, etc.). The economic crisis caused by the coronavirus also hit global economic and technological ties, led to their widespread fail in many geographical points of the planet, and increased the risk of fragmentation and regionalization of the global market. All this was adequately reflected in change of global demand for labor, in a significant transformation of the structure, size and location of employment, and the state of the labor market as a whole. At the same time, the global crisis did not equally affect the level of employment in different types of activity, the formation of demand for labor, the labor market as a whole; the structure of jobs and employment in individual professions, instead of a proportional change, was uneven - mainly in an asymmetric form.